Comparative analysis of the possible radical scavenging, antibacterial and anti-inflammatory effects of several extracts in case of Artemisia herba-alba and Juniperus communis gathered from Algeria's mountainous regions - Layadi, Ikram; Tlili, Mohammed Laid; Laiche, Ammar Touhami (Future Science, 2025)
This research reports a comparative analysis of the possible radical scavenging, antibacterial and anti-inflammatory effects of several ex-tracts in case of Artemisia herba-alba and Juniperus communis gathered from Algeria's mountainous regions. The plants extracts total phenolic acid content was ascertained using the Folin-Ciocalteu method, and their total flavonoid content was ascertained using the aluminum chlo-ride colorimetric test. By estimating their ability to remove free radi-cals using the DPPH method and the ferric reducing antioxidant power (FRAP) assay, their antioxidant capacity was assessed. Disk diffusion was used to measure the antibacterial activity against five strains of bacteria, and a protein denaturation assay was performed to examine the anti-inflammatory activity. A high polyphenol content of 104.54 ±0.35 mg GAE/g was observed in the hydroethanolic extract of Artemi-sia herba-alba, while a high flavonoid content of 17.05 ±0.13 mg QE/g was found in the hydroethanolic extract of Juniperus communis. Both species extracts showed important antioxidant activity in two separate tests, where the hydroethanolic extracts demonstrated effective action. The crude extracts showed positive antibacterial activity, especially the hydroethanolic extracts against Staphylococcus aureus and Klebsiella pneumoniae with a super inhibition on concentration 20 mg/ml. In the anti-inflammatory assay, the hydroethanolic extract of J. comminus with IC50: 23.58 ±0.02 μg/mL, has the most potent anti-denaturation effect on albumin. According to the study's findings, the hydroethanolic ex-tracts in case of Artemisia herba-alba and Juniperus communis gathered from Algeria's mountainous regions are possible sources of phenolic compounds with important natural antioxidant, antimicrobial and anti-inflammatory characteristics that may be employed in pharmaceutical products.